Macrocyclic dinuclear, helical, layered and 3-D Ag(i) complexes constructed from AgX (X = NO3− and ClO4−) and flexible bis(pyridyl) ligands with a chelating spacer: syntheses, structures and photoluminescence properties. Issue 12 (26th February 2015) - Huang, Jing; Deng, Zhao-Peng; Xiao, Ying-Hui; Huo, Li-Hua; Zhao, Shu-Nan; Ge, Fa-Yuan; Gao, Shan
Abstract : Eight novel Ag(i )-bis(pyridyl) complexes with diverse structures have been synthesized. Abstract : Reaction of AgX (X = NO3 − and ClO4 − ) and three flexible bis(pyridyl) ligands with a chelating spacer leads to the formation of eight novel Ag(i )-bis(pyridyl) coordination complexes: [Ag2 L1 (NO3 )2 ] n ·2 n H2 O (1 ), [AgL1 ] n · n ClO4 (2 ), [AgL2 ] n · n NO3 (3 ), [AgL2 ] n · n ClO4 (4 ), [Ag2 (H 2 L2 )2 ]·6ClO4 ·9H2 O (5 ), [AgL3 ] n · n NO3 · n H2 O (6 ), [AgL3 ] n · n ClO4 · n H2 O (7 ), and [Ag3 (L3 )2 (ClO4 )] n ·2 n ClO4 (8 ) (L1 = N, N ′-bis(pyridin-2-ylmethyl)propane-1, 3-diamine, L2 = N, N ′-bis(pyridin-3-ylmethyl)propane-1, 3-diamine, L3 = N, N ′-bis(pyridin-4-ylmethyl)propane-1, 3-diamine), which have been characterized by elemental analysis, IR, TG, UV-Vis DRS, PL, powder and single-crystal X-ray diffraction. Complex1 presents a (4, 4) layered motif which is furnished by the bridging ofL1 molecules and nitrate anions in μ4 (κ 1 N1:κ 1 N2:κ 1 N3:κ 1 N4) and μ2 (κ 1 O4:κ 1 O6) modes. With a different μ2 (κ 1 N1:κ 1 N2:κ 1 N3:κ 1 N4) mode, L1 molecules in complex2 join the adjacent Ag(i ) cations to form a helical chain structure. Complexes3 and4 also show helical chain structures with theL2 molecules displaying the same μ3 (κ 1 N1:κ 1 N2:κ 1 N3:κ 1 N4) mode. The protonation of –NH– groups in the chelating spacer leads to the formation ofH 2 L2 2+ cations which further results in a macrocyclic dinuclear motif in complex5 . Complexes6 and7 are 3-Dsvi-x nets with the counter-anions and lattice water molecules being encapsulated in the 1-D channels. Complex8 exhibits a snake-shaped chain with theL3 molecules presenting μ3 (κ 1 N:κ 1 N′:κ 1 N″:κ 1 N‴) mode. The structural diversities of complexes1–8 can be attributed to the coordination modes and conformations ofL1–L3 . The photoluminescence properties demonstrate that complexes1, 2 and5 exhibit ligand-based blue emission maxima from 455 to 462 nm at room temperature in the solid state.